2021
DOI: 10.1007/s00167-021-06601-z
|View full text |Cite
|
Sign up to set email alerts
|

A larger side-to-side difference in anterior knee laxity increases the prevalence of medial and lateral meniscal injuries in patients with ACL injuries

Abstract: Purpose The objective of this study was to investigate factors that inluence the prevalence of medial and lateral meniscal injuries at the time of anterior cruciate ligament (ACL) reconstruction in patients with ACL injuries. Methods Patients with ACL injuries at 9 institutions were enrolled in this multicentre study. Age, sex, duration between injury and surgery, pivot shift test grade, anterior knee laxity determined using the Kneelax 3 arthrometer, and other variables were assessed by logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Nevertheless, the impact of timing of surgery on meniscus damage in the isolated ACL reconstruction is well known in the literature. Many studies report a higher risk of overall meniscus tear, especially of the medial meniscus in delayed surgery compared to early surgery [6,8,10,[43][44][45][46]. The literature has widely demonstrated in long-term the superiority of meniscus repair in terms of function, return to sports and also cartilage protection, even more since high-energy knee injury increase the long-term risk of post-traumatic osteoarthritis [27,35,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the impact of timing of surgery on meniscus damage in the isolated ACL reconstruction is well known in the literature. Many studies report a higher risk of overall meniscus tear, especially of the medial meniscus in delayed surgery compared to early surgery [6,8,10,[43][44][45][46]. The literature has widely demonstrated in long-term the superiority of meniscus repair in terms of function, return to sports and also cartilage protection, even more since high-energy knee injury increase the long-term risk of post-traumatic osteoarthritis [27,35,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen cases including 9 patients suspected of ACL tears and 5 patients recovering after surgery were studied. The detailed clinical test results on these 14 cases using the Kneelax3 arthrometer and the WDS system are shown in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…This study is the first to investigate the relationship between the high‐grade pivot‐shift phenomenon and the asymmetry of L‐ATT and M‐ATT. The definition of ATT was proposed to represent the relationship between the tibia and femur [8], and has been used in the evaluation of knee stability and clinical outcomes before and after ACLR [2, 6, 23, 25]. Song et al [29] investigated the relationship between excessive ATT and clinical outcomes after ACLR and found that excessive preoperative ATT after ACL injury was associated with greater rotatory knee laxity two years after anatomic ACLR.…”
Section: Discussionmentioning
confidence: 99%